OntoGenesis: Uma Arquitetura para Enriquecimento Semântico de Web Data Services - Oliveira, Bruno C. N.; Siqueira, Frank (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
In recent years, many approaches and tools have emerged to assist in the semantic enrichment of Web Services. Many researchers have been directing efforts in enriching service descriptions. However, the automatic enrichment of data representations provided by Web Services has been of little concern in the literature. This work aims to present OntoGenesis, an architecture capable of constructing and evolving domain ontologies for data services and enriching their data with semantic concepts from such ontologies. The proposed solution also takes into account external semantic sources to enhance the reuse of well-known concepts by means of ontology property matching techniques. Preliminary results show the applicability of our approach under a scenario within real-world datasets.